2013
DOI: 10.2196/jmir.2787
|View full text |Cite
|
Sign up to set email alerts
|

Wikis and Collaborative Writing Applications in Health Care: A Scoping Review

Abstract: BackgroundCollaborative writing applications (eg, wikis and Google Documents) hold the potential to improve the use of evidence in both public health and health care. The rapid rise in their use has created the need for a systematic synthesis of the evidence of their impact as knowledge translation (KT) tools in the health care sector and for an inventory of the factors that affect their use.ObjectiveThrough the Levac six-stage methodology, a scoping review was undertaken to explore the depth and breadth of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 177 publications
(329 reference statements)
0
65
1
3
Order By: Relevance
“…In order to compare the study results to those of similar studies, labels from a validated taxonomy of social media adoption determinants were used. 11,44 Each belief was ranked from most to least frequently mentioned. The top 75th percentile of most frequently cited beliefs were considered "salient" in keeping with TPB methodology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to compare the study results to those of similar studies, labels from a validated taxonomy of social media adoption determinants were used. 11,44 Each belief was ranked from most to least frequently mentioned. The top 75th percentile of most frequently cited beliefs were considered "salient" in keeping with TPB methodology.…”
Section: Discussionmentioning
confidence: 99%
“…9 Collaborative writing applications (CWAs) are a category of social media that allows multiple authors to contribute synchronously and asynchronously to a single document. 10,11 New CWAs, such as Google Docs TM and wikis, are rapidly gaining popularity in medical education because they support free and open collaboration and decentralize content production. 4,7,9,[12][13][14][15][16][17][18] Constructivist learning principles support the use of social media in medical education.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing body of literature on the use of wikis in education and many researchers have recently published specifically within medical education [10]. A recent review article examining the use of wikis in medical education concluded that it has significant potential but is not yet well-studied [11].…”
Section: Wikis In Educationmentioning
confidence: 99%